Semi-Automatic Potato Peeler and Cutter: An initial development - Ahmad Faiz; M.H.A.R, Mantari; Roslan, M. S.; M.E.R, Indarah; M.I, Anuar; M.N, Mahadi; M. A. H, Mohamad (Multidisciplinary Applied Research and Innovation, 2020)
French fries are popular dishes in the world. Raw French fries preparation requires several methods that is tedious and time-consuming if it is done manually. The main intention of this project is to develop a semi-automatic machine that is able to peel and cut potatoes to French fries. The project is focused on small and medium-size potato, a portable and low fabrication cost machine, and targeted to small and medium enterprise industries. To achieve the project aims, a semi-automatic machine is developed that capable of peel and cut potato to French fries shape. The machine peeler uses an abrasive technique and rotation in removing the potato skins while the cutter uses a rotating crank with pusher connected to an electric motor to push potato to the cutting blade. The machine was tested to its functionality and the outcome was compare to the manual methods. For the comparisons, the machine capable of peeling up to 135% more potato weight and an average time improvement to cut potato is up to 62%. This machine is capable of reducing manpower effort in the preparation process and provides an improvement in production for small and medium scale industries.